STUDI TENTANG PENURUNAN JUMLAH ANAK TIDAK SEKOLAH DI KABUPATEN PEKALONGAN (Sebuah Kajian Analisis Jejaring) - Januardi Panji Sukmawan; Ari Subowo; Teuku Afrizal (Journal of Public Policy and Management Review, 2022)
Children Out of School is one of the problems that occur in the field of education. Pekalongan Regency is one of the regions in Central Java with a fairly high number of Children Out of School (ATS), which is 4346 children. Pekalongan Regency Government is trying to overcome this problem with the “Gerakan Kudu Sekolah”. This study aims to analyze the collaborative networking process in the “Gerakan Kudu Sekolah” as an effort by the Pekalongan Regency government to reduce the number of children out of school. The analysis in this study uses the theory of Collaborative Governance from Ansell and Gash. The study in this study used descriptive qualitative research with data collection methods of interviews, observations, and literature studies. Meanwhile, the data sources used are primary data and secondary data as well as other sources relevant to the research topic. The result is that the collaborative networking process at the face to face dialogue stage has obstacles to lack of operational funding support, at the trust building stage it has gone well, then at the commitment to process stage more commitment is needed from the Kesesi District, then at the sharing understanding stage the efforts made it is good enough but there are still indications of a lack of mutual understanding at the Kesesi District level, while at the intermediate outcomes stage at the Kesesi District level there has not been a short-term target set.